Functional diversity of active microbial mat communities inferred fromlipid biomarkers and metatranscriptomics - Campbell, Matthew Arthur (Curtin University, 2020)
Microbial mat communities possess extensive taxonomic and functional diversity, which drive high metabolic rates and rapid cycling of major elements. These ecosystems are considered as analogues to extinct geobiological formations dating back 3.5 billion years. This PhD project applied metatranscriptomic and lipid biomaker profiling to modem microbial mat communities, providing a comprehensive characterisation of the key active metabolic pathways, adaptation mechanisms and chemotaxonomic markers under different environmental conditions.